Who get paid higher? A study on wages decomposition between manufacturing and non-manufacturing workers in Indonesia - Arief Ibrahim; Nasri Bachtiar; Elvina Primayesa (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
In 2008, Indonesia became a member of the G20, and it is estimated that in 2030 it will be in the top seventh economic countries if it can keep growing. Nevertheless, high economic growth was followed by an inequality problem. This study will analyze the wage gap between manufacturing and non-manufacturing workers. Using Sakernas 2020 and the Mincer wage model regression, the result showed that all independent variables: age, level of education, gender, region of residence, marital status, toddler, disability status, and certificate training influence wages for both manufacturing and non-manufacturing workers. Next, the Blinder-Oaxaca method decomposes the wage gap between both groups. It is shown that manufacturing workers get higher wages than non-manufacturing workers because of differences in the characteristic of workers and also industry attributes which, in this case, capital intensity.